Isolation of Endophite Bacteria From The Stem Of Taxus (Taxus sumatrana) And Testing Its Potential As an Antimicrobial Compound Produce - Nanda Salma Rihadatul Aisy (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Aims: Indonesia as a country that has an abundance of flora. Most of the flora that grows is used as a medicinal plant. Types of drugs that are being developed are antimicrobial drugs. A plant that is currently being widely studied to produce antimicrobial compounds is Taxus sumatrana. Taxus plants have phenolic compounds, lignans, and flavonoids. One way to obtain these compounds is by isolating endophytic bacteria. The aim of this study was to isolate endophytic bacteria from T. sumatrana stems and test their potential as antimicrobial compounds. Methods: Taxus stems were surface sterilized using 1% and 2% hypochlorite. The sterilized tissues were grown in NA medium for 48 hours at room temperature. The growing bacteria were identified by macroscopic and microscopic methods. Antimicrobial activity test was carried out using the inoculation point diffusion method. Result: The results obtained were 2 isolates that could inhibit the growth of E. coli. There were 22 isolates of bacteria that were successfully isolated, 2 of which were BKB3 (2) and BBB1 (1) which could inhibit the growth of E. coli with a low inhibition zone.